Banff in Syracuse '87. - The Banff Centre School of Fine Arts, Banff (Banff : Contact, 1987)
Gutteridge, John ; Nordstrom, Kevin ; Eibner, Valerie ; Tang, Stanley ; Potvin, Francine ; Jamar, Edmond ; Hamill, Valerie J. ; Wollman, Nan ; Fuchs, Gloria Anna ; Stool, Laura ; Dumas, Lindsay P. ; Ibur, James M. ; Garber, Josh ; Rupp, Rebecca ; Manning, Les ; Harrison, Robert
Bannf in Syracuse '87 : The Banff Centre Ceramic Department Exhibition For The 1987 : National Council On Education For The Ceramic Arts Conference: "Ceramics In The Art World" Syracuse, New York, 1987
boek